1996
DOI: 10.1097/00000658-199612000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gas(less) Laparoscopy and Laparotomy on Peritoneal Tumor Growth and Abdominal Wall Metastases

Abstract: ObjectiveA tumor model in the rat was used to study peritoneal tumor growth and abdominal wall metastases after carbon dioxide (002) pneumoperitoneum, gasless laparoscopy, and laparotomy. Summary Background DataThe role of laparoscopic resection of cancer is under debate. Insufflation of the peritoneal cavity with C02 is believed to be a causative factor in the development of abdominal wall metastases after laparoscopic resection of malignant tumors. MethodsIn the solid tumor model, a lump of 350-mg CC-531 tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
164
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 286 publications
(174 citation statements)
references
References 23 publications
8
164
0
2
Order By: Relevance
“…Similar results were achieved by the same authors with a cell suspension of CC531. 34 These results are supported by Watson et al, 37 who demonstrated that the incidence of port-site metastases in a rat model was reduced after gasless laparoscopy compared with insufflation with CO 2 .…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Similar results were achieved by the same authors with a cell suspension of CC531. 34 These results are supported by Watson et al, 37 who demonstrated that the incidence of port-site metastases in a rat model was reduced after gasless laparoscopy compared with insufflation with CO 2 .…”
Section: Discussionmentioning
confidence: 57%
“…Jacobi et al 32 showed that the simple act of creating a CO 2 pneumoperitoneum caused increased tumor growth within the peritoneal cavity. Work by Bouvy et al 33,34 using both cell suspension and solid tumor models achieved similar results. In contrast, the results of Hubens and Eyskens 35 showed no difference in the rate intraperitoneal tumor growth between anesthetic controls and CO 2 insufflation.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The incidence of port site recurrences in IGBC after LC was 0-40 % in various reported series [13][14][15][16]. The proposed theories for port site recurrences include gallbladder perforation and bile spillage, direct physical and chemical influence of pneumoperitoneum, improper specimen extraction and increased abdominal pressure on tumour cell diffusion [13,14,17]. Paolucci et al reported an incidence of 17.1 % port site recurrence over a median period of 6 months after LC [14].…”
Section: Laparoscopic Cholecystectomy and Port Site Recurrencementioning
confidence: 99%
“…Although the mechanism of the abdominal wall recurrence is still unclear, it is speculated that two major factors may be involved: the systemic progression of the malignancy and the local implantation [2]. Laparoscopic handling of the tumour, perforation of GB, spurting of CO 2 gas containing tumour cells through the port site (so called Chimney Phenomenon) and extraction of the specimen without an endobag may be the risk factors [2].…”
Section: Discussionmentioning
confidence: 99%